Upgrading of bio-oil and subsequent co-processing under FCC conditions for fuel production. Issue 2 (14th December 2015) - Huynh, Thuan Minh; Armbruster, Udo; Atia, Hanan; Bentrup, Ursula; Phan, Binh Minh Quoc; Eckelt, Reinhard; Nguyen, Luong Huu; Nguyen, Duc Anh; Martin, Andreas
Abstract : NiCo/ZSM-5 revealed a bio-oil HDO deoxygenation degree of 39% and increase of the heating value of product oil to 33.3 MJ kg −1 . Abstract : Hydrodeoxygenation of fast pyrolysis oil was first investigated on bimetallic catalysts (homogeneous Ni–Co alloy) supported on various carriers (HZSM-5, HBeta, HY and ZrO2 ). The bimetallic catalyst 10Ni10Co/HZSM-5 outperformed the corresponding monometallic catalysts and Ni–Co supported on other support materials (HBeta, HY and ZrO2 ) with 39% deoxygenation degree and 37 wt% (wet basis) oil yield. 13 C-NMR spectroscopy, GC, GC-MS, and elemental analysis revealed that the chemical composition of the product changed significantly and the higher heating value increased substantially from 23.6 to 33.3 MJ kg −1 . The upgraded bio-oil was subsequently co-fed with a conventional feed (atmospheric distillation residue) using a commercial micro activity test setup under FCC conditions with an equilibrated commercial refinery catalyst to demonstrate a possible route for production of fuel from biomass. These tests showed similar conversion for both the conventional and co-processed feeds, whereas the latter case revealed a reduction of heavy cycle oil and a slight increase of gasoline, gas and light cycle oil yields.